ANALISIS MOTIVASI KERJA, KEPUASAN KERJA, DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) Studi Kasus pada Pegawai UPPD Kabupaten Purworejo Tahun 2019 - irawan irawan; Nur Wening (SEGMEN Jurnal Manajemen dan Bisnis, 2020)
This study uses descriptive quantitative methods. Data were collected using a questionnaire given to all employees of Regional Revenue Management Unit (UPPD) of Purworejo Regency, which amounted to 20 employees which were then analyzed. The results of the study showed that work motivation, job satisfaction and organizational citizenship behavior (OCB) at the Purworejo Regency Regional Revenue Management Unit (UPPD) were good. The highest mark of the work motivation variable is in the dimensions of physiological needs, and the lowest mark is in the dimensions of self-esteem or recognition needs. The highest mark of the variable work satisfaction is on the extrinsic dimension and the lowest mark is in the intrinsic dimension, while the organizational citizenship behavior (OCB) variable has the highest mark in the dimensions of conscientiousness, and the lowest mark is in the altruism dimension (helping behavior) . As an improvement effort, it is suggested that UPPD Purworejo Regency keep strive to maintain and improve the overall achievement of the target of tax and retribution receipts that have been set by the agency for future organizational progress. Key Words: Work Motivation, Job Satisfaction, And Organizational Citizenship Behavior (OCB)